ANALYSIS OF SITE MANAGEMENT IN THE PASSENGER TERMINAL BUILDING OF BANDAR DELI, BELAWAN PORT WITH A GREEN BUILDING APPROACH - Mega Gita Anastasia; Dara Wisdianti; Melly Adriana (Yayasan Sinergi Multidimensi Kreatif, 2024)
Deli Port Passenger Terminal , Belawan Port is one of form infrastructure important which is located in Medan City which is in the form of terminal port . This terminal own role For accommodation passenger between island in Sumatra. The existence of the Bandar Deli Terminal is certainly give impact positive in aspect economy and social . A study conducted by Aprilia (2024); Fadillah & Sinaga ( 2020) revealed that the passenger terminal This own arrangement less than optimal space and rumored can trigger failure operational sustainable building . Conditions This naturally not enough in accordance with hope government related importance adoption principle building green building in Indonesia for achieve the development agenda sustainable development that was initiated in Regulation of the Minister of PUPR No. 21 of 2021 concerning the Assessment of Green Building Performance and with attachments PUPR Circular Letter No.01/SE/M/2022 . ). In addition, the implementation of green building standards in Indonesia is expected to reduce the carbon footprint and increase energy efficiency by up to 30% compared to conventional buildings in accordance with the Energy Efficiency Guidelines for Buildings (Ministry of Energy and Mineral Resources, 2020). This study aims For analyze the site management of the Bandar Deli Terminal Building, Belawan Port based on the Indonesian Green Building Performance Assessment Parameters (BGH) which is one of the main variables in the BGH parameters. The method used is descriptive-qualitative, to describe the results of observations related to site management based on PUPR Circular Letter No.01/SE/M/2022 concerning Technical Instructions for Green Building Performance Assessment (BGH). The results of the study show that the management of the Bandar Deli Passenger Terminal site still does not meet the parameters in the Site Management variable in accordance with the Green Building (BGH) standards, with a score of 14 points out of 38 points so that further evaluation is needed in research on other variables and also possible improvements to support the achievement of Green Building (BGH) standards in Indonesia.